If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + 48 = 6x Reorder the terms: 48 + X = 6x Solving 48 + X = 6x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-48' to each side of the equation. 48 + -48 + X = -48 + 6x Combine like terms: 48 + -48 = 0 0 + X = -48 + 6x X = -48 + 6x Simplifying X = -48 + 6x
| -5p+5(-7p+2)= | | 1/2x+1/3x= | | 2x=4.2 | | 8m-12=-7 | | 1/5d=70 | | =x^2+1 | | 2x+2y=156 | | 16t^2+96t-160=0 | | 11m=-16+38 | | sinx=105 | | 2x-5x+9=x-9+18 | | x*12+28=x*3+217 | | -17+41=-4(x+8) | | 4*14=16 | | 2*17=7 | | 1.16x=140 | | 3x^2+3Y^2-12x+8y+12=0 | | (6.50-1.75)x=33.25 | | 0.5(4z+6)+10.22=0.7(4z-4) | | 2c+4p=26 | | -2n*-2n= | | 6.50x-1.75=33.25 | | x^4-4=9 | | 6(z+1)=7z-9 | | 6.50-1.75x=33.25 | | 7x+35=8x-6 | | 1/5x=4/25 | | -5=14+x | | 7(x+5)=8x-6 | | -7b*6b= | | 9y-21=15 | | 16/x=40/25 |